EFFECT OF AN INTERVENTION IN DECREASING OF THE PERCEPTION OF BARRIERS FOR BICYCLE USE IN THE COMMUTING TO WORK - Ana Carolina Belther Santos; Cassiano Ricardo Rech; Ilca Maria Saldanha Diniz; Elusa Santina Antunes de Oliveira (Journal of Physical Education)
ABSTRACT This study investigated the effect of an intervention on perceptions of barriers for the bicycle use in commuting to work by industrialists. 876 men (mean age = 35.4 ± 9.5 years) from a metallo-mechanical company participated. The sample was randomized into a control and intervention group (438 participants in each group) considering the use or not of the bicycle when commuting to work. The intervention had 23 meetings of approximately 30 minutes each, spread over six months, based on the Transteoric Model of Behavior Change (TMBC). The perception of barriers to bicycle use was assessed using the “scale to assess the perception of barriers to bicycle use”. Descriptive statistics, chi-square, Wilcoxon test, Kruskal-Wallis and Mann-Whitney were applied for analysis, adopting p < 0.05. There was a statistical decline in perception of barriers to bicycle use in the intervention group (Z = -2.218; p = 0.027). When stratified by age group, greater effectiveness of the intervention was observed in reducing in the perception of barriers in individuals aged 30-39 years (Z = -2.637; p = .008). For the other age groups, there were no significant differences. It is concluded that interventions based on TMBC are effective to decrease the perception of barriers for bycicle use in the commuting to work.